ALISKIREN (RENIN INHIBITOR) AS THE RECENT ANTIHYPERTENSIVE MODALITY - Luh Gde Primahatini Suaka Putri (E-Jurnal Medika Udayana, 2013)
Hypertension is a chronic disease which is commonly found. Many people pay attention on it. The prevalence of hypertension all over the world is almost one billion, of which mortality is approximately 1,7 million each year. The renin-angiotensin-aldosterone system (RAAS) has an important role which caused hypertension. Two kind of drugs which work on RAAS and recently used widely are angiotensin-converting enzyme inhibitors (ACEI) and angiotensin receptor blocker (ARB). Both of them have weakness in blocking RAAS and their side effects. Renin is an important component in RAAS and has specificity for angiotensinogen. Renin inhibitors can block RAAS at the highest level. Aliskiren is the first renin inhibitor which can be orally given and has developed until the clinical trial of the third phase. The disadvantages of ACEI and ARB can be solved because of the aliskiren.